ANGER AND CARDIAC REACTIVITY. ADAPTATION TO A REAL LIFE STRESS SITUATION - Breva Asensio, Alicia; Espinosa, Matilde; Palmero Cantero, Francisco (Anales de Psicología / Annals of Psychology, 2000)
The objective of our work is centered in establishing the possible existent relationship between the angerhostility construct and the cardiac activation and reactivity. The scientific studies on the topic obtain heterogeneous results, great part of them due to the type of experimental task designed to detect differences among groups. In our work, a task of real stress, an exam, has been used, that allows to better detect the differences among groups of subjects. For it, we have conformed two groups of subjects on account their punctuations in the Composite Scale, obtained from the Cook and Medley Hostility Inventory (Ho): group of high anger-hostility and group of low angerhostility. Our hypotheses are the following ones: in the first place, we outline that the subjects that score high in the anger-hostility variable they will present bigger heart activation in the three phases of the designed experiment, that is, adaptation, task and recovery; in second place, we outline that the subjects that score high in anger-hostility variable they will take more time in adapting to the demands of the task, presenting a slower recovery of their basal levels. The obtained results confirm the two outlined hypotheses.